The Influence of Workplace Well-Being and Employee Engagement on Organizational Citizenship Behavior Through Work Motivation at the Indonesian Aviation Academy Banyuwangi - Iswahyudi, Prasetyo; Hari Kurniawanto; Nur Halimah; Khoirunnisa Larasati (International Journal of Natural Science Studies and Development (IJOSS), 2025)
This study examines the influence of workplace well-being and employee engagement on Organizational Citizenship Behavior (OCB) with work motivation as a mediating variable at the Indonesian Aviation Academy (API) Banyuwangi. The problem stems from a condition where employee extra-role work behavior is not optimal, so efforts are needed to understand psychological factors and engagement that can increase employee voluntary contributions to the institution. The results showed that workplace well-being and employee engagement have a positive and significant effect on work motivation. In addition, work motivation was proven to be able to mediate the influence of workplace well-being and employee engagement on increasing OCB, thereby strengthening the relationship between variables in supporting organizational performance. Overall, this study concludes that workplace well-being and employee engagement are important factors in driving motivation and extra-role work behavior. These findings have practical implications, necessitating HR policies that focus on creating a healthy, inclusive, and motivating work environment to strengthen a positive work culture. Furthermore, this study also provides theoretical contributions, enriching our understanding of the role of work motivation as a connecting mechanism in the context of aviation vocational education.